Near Infrared Metal-insulator-metal Surface Plasmon Resonances for Refractive Index Sensors - Hoang, Thi Hong Cam; Ha, Tuan Minh; Pham, Van Dai; Ngo, Quang Minh (Communications in Physics, 2022)
This work reports the optical properties of surface plasmon resonance (SPR) based on the metal-insulator-metal (MIM) structure towards a refractive index sensor. The MIM-SPR structure operating near infrared region consists of lateral periodicity of subwavelength gold patterns placed on a stack of thin silica spacer and silver film (acting as a reflector) on a silicon substrate. The reflection spectra and the electric field distributions of MIM-SPR structures can be tuned by modifying the geometrical properties and have been numerically investigated by using Lumerical’s finite-difference time-domain (FDTD) solutions. The square lattice configuration of 1200 nm to 1400 nm pitch of gold micro-disks of thickness from 80 nm to 120 nm have been conducted. The size of these considered gold patterns, i.e., the diameter of the micro-disks is in the range of 900 nm to 1000 nm. The proposed MIM-SPR structure possessing sensitivity of 370 nm per refractive index unit (RIU), can be applicable for a wide variety of plasmonic sensing, in particular for refractometric biosensors.